Neck Circumference May Be a Better Alternative to Standard Anthropometric Measures - Kaumudi Joshipura; Francisco Muñoz-Torres; José Vergara; Cristina Palacios; Cynthia M. Pérez (Journal of Diabetes Research)
This paper evaluates neck circumference as a metabolic risk marker. Overweight/obese, nondiabetic Hispanics, 40–65 years old, who are free of major cardiovascular diseases, were recruited for the San Juan Overweight Adults Longitudinal Study (SOALS). Baseline exams were completed by 1,206 participants. Partial correlation coefficients (r) and logistic models adjusted for age, gender, smoking status, and physical activity were computed. Neck circumference was significantly correlated with waist circumference (r=0.64), BMI (r=0.66), and body fat % (r=0.45). Neck circumference, highest (compared to lowest) tertile, had higher association with prediabetes: multivariable OR = 2.30 (95% CI: 1.71–3.06) compared to waist circumference OR = 1.97 (95% CI: 1.48–2.66) and other anthropometric measures. Neck circumference showed higher associations with HOMA, low HDL-C, and triglycerides, multivariable OR = 8.42 (95% CI: 5.43–13.06), 2.41 (95% CI: 1.80–3.21), and 1.52 (95% CI: 1.14–2.03), but weaker associations with hs-CRP and hypertension, OR = 3.61 (95% CI: 2.66–4.90) and OR = 2.58 (95% CI: 1.90–3.49), compared to waist circumference. AIC for model fit was generally similar for neck or waist circumference. Neck circumference showed similar or better associations with metabolic factors and is more practicable than waist circumference. Hence, neck circumference may be a better alternative to waist circumference.